Strategic approach to community regeneration with emphasis on the integration of art, culture and historical values as catalysts of development - Saksono, Ratnawati (College of Architecture, University of the Philippines, Diliman, 2003)
The recent development of San Isidro, a 4th class municipality in Nueva Ecija, is one of those that can inspire other similar towns in increasing the working efficiency and effectiveness of its community development through focused vision and good governance of its Local Government Unit. San Isidro itself has a glorious past worth recollecting. There was a time when it was the premier town of the province of Nueva Ecija. It was the capital of Nueva Ecija up to 1912 when the seat of the government was transferred to Cabanatuan. In 1905 the first Philippine high school outside Manila was built in San Isidro. But with the passing away of Spanish and American sovereignty from the country, the glory that was once San Isidro slowly faded away. Somehow the town could not catch up with development surrounding it. Commercial establishments did not prosper, new business ventures did not come in. The youths left to the bigger cities for further studies oftentimes could not come back and work in San Isidro as they could not use the skill or education they had attained. Not surprising as the main preoccupation of the population is farming and rice is their main agricultural product. Many beautiful residences of prominent fam,ilies are left to decay.The market that was once the most important in the province was being abandoned even by its own community, preferring to go to the Gapan market nearby. A quick walk around the market is enough to understand why. The glory that San Isidro once had is left to the memories of the old folk of the town. In 1999, with the concerted efforts of the Local Government Unit headed by Mayor Sonia Lorenzo, San Isidro through a committee called TAMA ARC (Tabon Mangga Agrarian Reform Community) received loan packages under the DAR-ADB ARCP programs for concreting the farm to market road. This was one of the most crucial needs of the farmers as they had found it difficult to transport their products such as rice, livestock, fisheries, etc. from their respective farms to market. With the success of this project, the Local Chief Executive, Mayor Sonia Lorenzo, did not just stop with just these projects but instead used these as a leverage to partner with service and resource providers. Today, TAMA ARC is now a convergence area of many Programs and Projects of the government and private sectors. The ARC received other projects such as a) Likod - Bahay Kaunlaran for planting of agricultural crops and livestock raising; b) Kapamahalaang Barangay sa Kalusugan dealing with residents' health and related needs; c) Family Self-Employment Programs providing training, technical assistance and business loan for low incmoe families; d) Pamayanang Dalub - aralan ng Buhay -Community Learning Center for life and to top it all e) the Land Bank of the Philippines approved the "Abot Kaya Pabahay sa Magsasaka Farmers' Housing. These are all packaged under the San Isidro Anti Poverty Program (SIAPP). Grand efforts in developments such as this however needs to be visibly seen in terms of the physical facade of the town for several reasons: a) to give awareness to the community of the progress that is happening in thier community; b) as promotions to the outsiders of the progress of the town which in complement, could invite more people to come and attract investors or donors; c) it instills the sense of pride to the residents of the town. All these reasons have a long term benefit, not only economically, but also culturally, socially and environmentally. This paper aims to tie in a strategic approach to physical planning by emphasizing on its strengths on art, culture and historical heritage to complement the progress of the town as a result of the development programs that is already on-going. Development programs lead to progress. However, this progress does not necessarily lasts as progress also brings with it problems; to the environment, the socio-cultural well being of the people. Thus, it is important that physical planning comes hand in hand as the town/city progresses to anticipate the problems caused by development and to complement development itself.